Nation branding and integrated marketing communications: an ASEAN perspective - Dinnie, K.; Melewar, T.C.; Seidenfuss, K.U.; Musa, G. (Emerald, 2010)
This paper aims to examine the extent to which the nation branding activities of export promotion organisations (EPOs), investment agencies (IAs), national tourism organisations (NTOs) and embassies follow the principle of coordination that characterises an integrated marketing communications approach.